DINAMIKA MASYARAKAT MULTI ETNIK DAN MENTALITAS PETANI DALAM MEMBANGUN KETAHANAN PANGAN DI KOLAKA TIMUR - Nurti, Yevita; Jers, La Ode Topo; Arimbawa, Putu; Efriani, Efriani; Alias, Alias; Marhadi, Akhmad; Syahrun, Syahrun; Ashmarita, Ashmarita (Department of Anthropology, Faculty of Social and Political Sciences, Hasanuddin University., 2024)
This research explores the cooperation of multiethnic communities and the formation of a farmer mentality in East Kolaka District, Southeast Sulawesi Province, in building food security. The purpose of this study is to understand how the interaction between diverse ethnic groups in East Kolaka society affects the way farmers manage agricultural resources and shape their mentality regarding agriculture so as to realize food security. The cultural interaction among multi-ethnic communities serves as a collective strength in East Kolaka District to address food scarcity and to build a food security system, which has not been optimally examined and elucidated in previous studies. Using qualitative approach, data was collected using in-depth interview and observation. This study was conducted in East Kolaka District, Southeast Sulawesi Province. The total number of informants is fourteen, including rice farmers, community leaders, members of farmer groups, agricultural extension workers, and village and sub-district government officials. The study shows that various ethnic groups have unique agricultural practices, traditional techniques, and different local knowledge. The interaction between these groups has resulted in an exchange of knowledge and experience, which in turn affects the mentality of farmers positively in the face of environmental and social changes, and can build their food security and even surplus. These findings have important implications in efforts to improve food security and agricultural sustainability in East Kolaka, as well as encourage inter-ethnic cooperation in the context of agriculture. This research contributes to a deeper understanding of the complexities of multi-ethnic societies and how interactions between these groups can shape peasant mentalities. The findings of this study can be an input for policymakers in designing more inclusive and sustainable strategies in agricultural resource management in similar regions.